2017
DOI: 10.1038/s41598-017-01016-8
|View full text |Cite|
|
Sign up to set email alerts
|

Perfluorooctanesulfonate (PFOS)-induced Sertoli cell injury through a disruption of F-actin and microtubule organization is mediated by Akt1/2

Abstract: PFOS (perfluorooctanesulfonate, or perfluorooctane sulfonic acid) is an anthropogenic fluorosurfactant widely used in consumer products. While its use in Europe, Canada and the U.S. has been banned due to its human toxicity, it continues to be used in China and other developing countries as a global pollutant. Herein, using an in vitro model of Sertoli cell blood-testis barrier (BTB), PFOS was found to induce Sertoli cell injury by perturbing actin cytoskeleton through changes in the spatial expression of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 83 publications
0
35
0
Order By: Relevance
“…For instance, both actin-based TJ, basal ES, and gap junction, as well as intermediate filament-based desmosome are noted at the Sertoli cell-cell interface when these cells are cultured in vitro. Since p-FAK-Tyr407 is one of the signaling proteins shown to promote Sertoli cell BTB integrity [18, 40], it is not surprising that PFOS-induced Sertoli cell TJ-permeability barrier disruption was associated with a considerably down-regulation of p-FAK-Tyr407 in rat Sertoli cells [13, 41]. PFOS was also shown to perturb the organization of the actin- and microtubule (MT)-based cytoskeletons in rat (and also human Sertoli cells ( Figure 1B ) ), suggesting that FAK may also be involved in cytoskeletal organization.…”
Section: Role Of Fak In Pfos-mediated Sertoli Cell Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, both actin-based TJ, basal ES, and gap junction, as well as intermediate filament-based desmosome are noted at the Sertoli cell-cell interface when these cells are cultured in vitro. Since p-FAK-Tyr407 is one of the signaling proteins shown to promote Sertoli cell BTB integrity [18, 40], it is not surprising that PFOS-induced Sertoli cell TJ-permeability barrier disruption was associated with a considerably down-regulation of p-FAK-Tyr407 in rat Sertoli cells [13, 41]. PFOS was also shown to perturb the organization of the actin- and microtubule (MT)-based cytoskeletons in rat (and also human Sertoli cells ( Figure 1B ) ), suggesting that FAK may also be involved in cytoskeletal organization.…”
Section: Role Of Fak In Pfos-mediated Sertoli Cell Injurymentioning
confidence: 99%
“…Overexpression of p-FAK-Y407E in Sertoli cells also blocked the PFOS-induced F-actin disorganization so that the TJ adhesion protein complex occludin-ZO-1 that utilized actin for attachment could remain at the Sertoli cell-cell interface following PFOS treatment to support the Sertoli cell TJ-barrier function [13]. A subsequent study has shown that the PFOS-induced down-regulation of p-FAK-Try407 is associated with a considerable down-regulation of Akt1/2, notably p-Akt1-T308, p-Akt1-S473 and p-Akt2-S474 [41], illustrating both FAK and Akt1/2 signaling proteins may be involved in PFOS-induced Sertoli cell injury.…”
Section: Role Of Fak In Pfos-mediated Sertoli Cell Injurymentioning
confidence: 99%
“…This effect of PFCs on spermatozoa tyrosine phosphorylation has not been reported previously. Gao et al (2017) [ 20 ] determined that PFOS damages the Sertoli cells by disturbing actin cytoskeleton by down-regulating p-Akt1-S473 and p-Akt2-S474. They added that SC79 (an Akt1/2 activator) blocked PFOS-induced Sertoli cell injuries by rescuing PFOS-induced F-actin disorganization.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PFOS and PFHxS have been shown to reduce morphologically normal spermatozoa, while PFOS increased spermatozoa tail abnormalities and decreased testosterone levels and motility [ 15 , 16 , 17 ]. In mice [ 18 ], PFOS diminished serum testosterone concentrations and epididymal spermatozoa counts, while in rats it damaged the blood-testis barrier function by disrupting the tight junction-permeability barrier of Sertoli cells [ 19 , 20 ]. In zebra fish, it decreased spermatozoa quality and had an estrogenic effect that increased estradiol levels but decreased testosterone in the juvenile phase [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its toxic effects have begun to emerge, initially detected in wildlife and then in humans, and they include defects in development, cancer, endocrine disruption, neonatal mortality [10,11], and an increased risk of attention-deficit hyperactivity disorder [12]. PFOS was also found to induce Sertoli cell injury by perturbing actin cytoskeleton through changes in the spatial expression of actin regulatory proteins [13] and the organization of F-actin in Sertoli cells [14]. With this study we aim to investigate how PFOS affects ezrin and fascin 1 expression pattern and prevent the organisation of F-actin bundling in BTB.…”
Section: Introductionmentioning
confidence: 99%